Isoorientin attenuates benzo[a]pyrene-induced colonic injury and gut microbiota disorders in mice. (December 2019) - He, Shenyuan; Li, Xueyi; Li, Cuiqin; Deng, Hong; Shao, Yuyu; Yuan, Li
Abstract: Benzo[ a ]pyrene (BaP, most toxic polycyclic aromatic hydrocarbon) is a global food-borne pollutant, and is associated with many diseases and gut microbiota disorders. The present study was designed to investigate the protective effects of isoorientin (ISO), a flavonoid compound in the human diet, on BaP-induced colonic damage and gut microbial disorders in mice. ISO was administered orally to mice at doses of 20 mg/kg body weight before BaP challenge (oral administration, 50 mg/kg body weight). The results revealed that ISO suppressed the BaP-induced reduction of body weight in mice, and it also prevented colonic damage, as evidenced by the increase in colon total superoxide dismutase (T-SOD) and glutathione peroxidase (GSH-Px) activities, and the decrease in colon malonaldehyde (MDA) and hydrogen peroxide (H2 O2 ) levels, compared to BaP-treated mice. Meanwhile, we used 16S rRNA gene sequencing to investigate the impact of BaP with or without ISO on the colon contents associated bacteria in mice. ISO could relieve the BaP-induced change in the abundance of gut microbiota, especially the genera of Feacalibaculum, Lactobacillus, Acinetobacter, Desulfovibrio and Alistipes . And ISO ameliorated BaP-induced microbiota metabolic disturbance, especially the metabolic pathways of LPS and sulphur compounds. In conclusion, our findings indicated that ISO could be of significant advantage in suppressing the colonic injury and the gut microbiota disorder induced by BaP. Graphical abstract: Unlabelled Image Highlights: Isoorientin suppresses the benzo[ a ]pyrene-induced reduction of body weight in mice. Isoorientin prevents colonic damage of mice induced by benzo[ a ]pyrene. Isoorientin relieves the benzo[ a ]pyrene-induced change in the abundance of gut microbiota in mice. Isoorientin ameliorates benzo[ a ]pyrene-induced microbiota metabolic disturbance in mice.